I have gone thru all my examples to find a solution to this problem... but no matter what I do I seem to get it wrong... I need help on how to simplify the following:
(xy + wz)(wx + yz)
This is what I have:
= xy'wx' + xy'yz' + w'zwx' + w'zyz' (Distributive)
= x' + y + w' + xx' + y + y' + zw + z' + w' + xw + z' + y' + z (DeMorgan's)
= .... (I keep simplifying)
= 1 (I know this isn't right...)
(xy + wz)(wx + yz)
This is what I have:
= xy'wx' + xy'yz' + w'zwx' + w'zyz' (Distributive)
= x' + y + w' + xx' + y + y' + zw + z' + w' + xw + z' + y' + z (DeMorgan's)
= .... (I keep simplifying)
= 1 (I know this isn't right...)